Advances in the proof test for certification of bonded repairs – Increasing the Technology Readiness Level. (January 2016) - Baker, Alan; Gunnion, Andrew J.; Wang, John; Chang, Paul
Abstract: The availability of an efficient, cost-effective repair technology is an important maintenance requirement to restore structural integrity to metallic and composite airframe structures damaged in service. Generally repair involves attachment of a reinforcing structural element or patch to replace the damaged load path. Traditionally, the reinforcements are attached to the structure with rivets or bolts; however, attachment by adhesive bonding offers many structural and cosmetic advantages. However, bonded repairs of primary structure are very difficult to certify this is because available non-destructive procedures, such as ultrasonics or thermography are unable to detect weak adhesive bonds. In view of the limitation of non-destructive inspection an alternative approach is to directly apply stress to the actual repair bond region or to a very close simulation of the region. In this paper, further work is documented on a proof test of bonded repair coupons (BRCs) that are bonded to the parent structure at the same time as bonding of the repair patch. Therefore, the BRCs are close representation of the actual repair bond strength. To assess the bond strength, immediately after patch application and also possibly through the life of the repair, the BRCs are subject to a previously determined proof load in torsion. The aim of the study is to improve the Technical Readiness Level of the test when applied to various parent-structure/patch-repair systems, including carbon-epoxy/carbon-epoxy; aluminium/boron-epoxy and aluminium/aluminium. Improved BRC application methods were developed to increase the reliability and consistency of the results, and sensitivity to cure condition, surface treatment, contamination, and fatigue damage were evaluated. A detailed finite element (FE) study was undertaken to: a) simulate stresses in the BRC, adhesive and parent structure during the proof test, b) compare the stresses in the patch and BRC when the parent material is under stress and c) investigate the influence of BRC proximity to the patch tip when the parent material is under stress. A conclusion from the FE analysis and fatigue study was that a BRC with the appropriate ply configuration could represent the bondline stresses experienced at the patch tip, and hence could also be used to monitor fatigue damage.